2021
DOI: 10.1021/acs.inorgchem.1c03040
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Two-Dimensional Metal–Organic Framework Nanosheets with Large π-Conjugated System: Design, Synthesis, and Detection of Anti-Inflammatory Drugs and Pesticides

Abstract: Two-dimensional (2D) metal–organic framework (MOF) nanosheets, with largely exposed surface area and highly accessible active sites, have emerged as a novel kind of sensing material. Here, a luminescent 2D MOF nanosheet was designed and synthesized by a facile top-down strategy based on a three-dimensional (3D) layered MOF {[Zn­(H2L)­(H2O)2]·H2O} n (Zn-MOF; H4L = 3,5-bis­(3′,5′-dicarboxyphenyl)-1H-1,2,4-triazole). With a large π-conjugated system and rigid planar structure, ligand H4L was elaborately selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 59 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Liu et al synthesized a 2D nanosheet of Zn-MOF, which had a LOD of 0.2 ppm and K sv of 4.32 × 10 4 M –1 toward DS sensing. The PL quenching of the 2D-nanosheet of Zn-MOF by DS was ascribed to the electron transfer from the MOF to DS …”
Section: Fluorescence-driven Sensing Of Various Pharmaceutical Drugs ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al synthesized a 2D nanosheet of Zn-MOF, which had a LOD of 0.2 ppm and K sv of 4.32 × 10 4 M –1 toward DS sensing. The PL quenching of the 2D-nanosheet of Zn-MOF by DS was ascribed to the electron transfer from the MOF to DS …”
Section: Fluorescence-driven Sensing Of Various Pharmaceutical Drugs ...mentioning
confidence: 99%
“…The PL quenching of the 2D-nanosheet of Zn-MOF by DS was ascribed to the electron transfer from the MOF to DS. 144 5.14. Antibacterial Drugs.…”
Section: Balsalazide Disodium (Bal) and Colchicine (Col)mentioning
confidence: 99%
“…Owing to the weak hydrogen-bonding interactions between the 2D Cd-L coordination networks, it is probable that the prepared Cd-1 can be exfoliated into nanosheets induced by solvents through ultrasonication. According to previous studies, the solvents have an important effect on the exfoliation of layered CPs. , Thus, we first surveyed some common solvents, including water, methanol, ethanol, isopropanol, DMF, acetonitrile, acetone, ether, ethyl acetate (EA), tetrahydrofuran (THF), and triethylamine by soaking the pristine crystals of Cd-1 in these solvents under ultrasonication. , The suspension obtained in isopropyl alcohol exhibited a significant Tyndall effect upon irradiation with an incident laser light beam, suggesting the formation of the Cd-1 nanosheet ( Cd-1-NS ). In order to further illustrate the morphology of the prepared Cd-1-NS , scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM) measurements were conducted, and the results clearly demonstrated the formation of 2D nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] The 2D MOF nanosheets hold the structural characteristics of both bulky MOFs and 2D materials, such as versatile compositions and functions, exposed surface area, innumerable accessible surface-active sites, and nanoscale thickness, which were facile for the interaction with substrate molecules, affording improved performance in catalysis, sensing, separation, etc. [27][28][29][30][31][32] The significance of the synthesis of 2D MOF nanosheets was greatly highlighted by these attractive properties and applications. [33][34][35] However, few studies on pollutant capture by 2D MOF nanosheets have been reported thus far.…”
Section: Introductionmentioning
confidence: 99%